The Role of Inquiry-Based Interactive Demonstration Learning Model on VIII Grade Students’ Higher Order Thinking Skill - Erni Yulianti; Itsna Yunida Al Husna; Susilowati Susilowati (Universitas Negeri Yogyakarta, 2018)
Teacher’s domination in teaching science subject is still found in many schools, including junior high schools. Since then, students experience a lack of direct observation leading to not only their low conceptual understanding, but also their higher order thinking ability. Therefore, the implementation of a proper learning model becomes a crucial breakthrough. In this present paper, we focus on the influence of learning model with inquiry level of interactive demonstration (as the experimental class) and discovery-based learning model (as the control class) on the VIII grade students’ higher order thinking ability. We used posttest only control group design by means of using 20 validated multiple choice questions with reliability of 0.872. The data analyses were completed comprehensively, from normality test to t-test on students’ ability. As the conclusion, according to those data analyses, students’ higher thinking skill is better when students are thought by interactive demonstration rather than by discovery learning.